Los cánones del retrato femenino en el Canzoniere. Difusión y recreación en la lírica española del Renacimiento - Manero Sorolla, Mª Pilar (Cuadernos de Filología Italiana, 2005)
This article exposes synthetically how the old canonic laws of the Middle Ages literary feminine portraits were innovated by Petrarch, the creator of a selective and modifyied conception of female beauty. Among his works, the Canzoniere, specially, established the new canons for the European Renaissance and Mannerism Poetry. The present study illustrates the diffusion and recreation of the petrachist canons in the Sixteenth Century Spanish Lyric Poetry in some texts of Garcilaso de la Vega, Camões (Spanish), Cetina, Francisco de Figueroa, Francisco de la Torre and Herrera, among others poets.